INTERNET USAGE AND SELF-REGULATED LEARNING ASSESSMENT AT JUNIOR HIGH SCHOOL STUDENTS IN TASIKMALAYA CITY, INDONESIA - El Akbar, R. Reza; Ratnaningsih, Nani; Hidayat, Edi (APTIKOM Journal on Computer Science and Information Technologies, 2019)
describes the pattern of relationship between internet usages on students, on the assessment of aspects of selfregulated learning. The aspect of self-regulated learning measured from 10 aspects. This study discusses the effects ofgender, the categories of schools (excellent schools and regular school), the total value of self-regulated learning andthe value of math exams. In brief, the research stages consist of three stages. The first stage of research is to createand retrieve the questionnaire data. The goal is to obtain all things related to internet usage, as well as measure aspectsof self-regulated learning assessment. The second stage of treatment on students. This treatment time is done for fourmonths, where students follow the math lesson with self-regulated learning method. Students provided with multimediadevices, textbooks and other. The third stage is the assessment or math test. The analytical method used is qualitativemethod with descriptive statistical approach. The results obtained that the dominant male students using internet forgames tend to have greater Aspects of Finding and Utilizing Relevant Learning Resources. While female, tend to bedominant in aspects of Evaluating Learning Processes and Results. The average mathematical exam results, in studentswho often use the game tend to have a higher value, compared with other students who often use social media.